Relationship Between Equal Opportunity, Training and Employee Performances (International Journal of Scientific Research in Science and Technology, 2024)
The purpose of this paper is to look into the relationship and problem of equal employment opportunities in the HR recruitment and selection process. Because both HR managers and employees are involved in these processes, this research is carried out separately among them. As a result, it’ll be determined whether both parties agree on the existence of this concept. Equal employment opportunities are essential for any business and play a key function in attracting qualified employees. One of the main path to achieving social justice in the community is the principle of equal opportunity among employees. As a result, equal opportunity is greater than a slogan to be shouted or a claim to be made; it is a political will and a national strategy. Many researchers have paid attention to this study in the modern era, particularly in terms of equal pay and employment equity training in the administrative center. In this regard, one of the primary aim of this paper is to conduct a review and analysis of the empirical literature on the effect of equal opportunity among employees on employee performance based on previous research conducted by the researchers. Equal opportunities are a curial detail among employees in administrative center in order to enhance overall performance and achieve social justice in the community. This studies goals to identify the contributions and the consequences of equal opportunities on the employee overall performance in administrative center. The data was analysed using SPSS (Statistical Package for Social Science) version 25 for Windows. The results of the regression analysis showed significant and positive impact on equal opportunities and employee overall performance in the organization of its 4 dimensions. Thus, this paper is significance as its concerning on the future guidelines as well as addresses other variables in the administrative center which can be utilized to enhance this area.